Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1186/1751-0147-50-51
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of epilepsy in the Belgian shepherd variants Groenendael and Tervueren born in Denmark 1995–2004

Abstract: Background: The Belgian shepherd Groenendael and Tervueren is believed to be at higher risk of developing epilepsy than dogs of the common population. This epidemiological study was designed to estimate the prevalence of epilepsy in the Danish population of Groenendael and Tervueren born between 1995 and 2004. Furthermore, it was the intention to describe the clinical manifestation (seizure types and phenomenology) of epilepsy and to identify risk factors for euthanasia once the dog was diagnosed as having epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 28 publications
(31 reference statements)
11
71
1
2
Order By: Relevance
“…ES can result in the life‐threatening condition of SE. Yet, the prevalence of ES and SE in the hospital population is rarely described in veterinary medicine, and currently only limited data on the prevalence of these conditions are available 20 . In human medicine, between 0.8 and 1% of the human population, respectively, are estimated to suffer from a form of epilepsy during their lives 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…ES can result in the life‐threatening condition of SE. Yet, the prevalence of ES and SE in the hospital population is rarely described in veterinary medicine, and currently only limited data on the prevalence of these conditions are available 20 . In human medicine, between 0.8 and 1% of the human population, respectively, are estimated to suffer from a form of epilepsy during their lives 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Intact Belgian shepherd dogs with epilepsy have also been found to have an increased risk of being euthanased because of epilepsy compared to neutered dogs (Berendt and others 2008), which the authors attributed to a reduced seizure frequency in neutered dogs.…”
Section: Quantity Of Lifementioning
confidence: 99%
“…An early study found the prevalence of epilepsy for BT in the United States to be 17% [3] which is higher than the estimated prevalence of 9.5 - 11.1% for BT and BS in Denmark [2]. In the general dog population, the prevalence of epilepsy is estimated to be approximately 1.0% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Using the ILAE system, Berendt [2] completed a comprehensive survey of epilepsy in the Belgian shepherds of Denmark and reported the prevalence of epilepsy at 9.5% (49 out of 516 dogs). Of these 49 epileptic dogs, 71% of the dogs experienced either primary or secondarily generalized seizures.…”
Section: Introductionmentioning
confidence: 99%